Education Policies in the 21st Century Comparative Perspectives - Akgün, Birol; Alpaydın, Yusuf (Maarif Global Education Series,, 2022)
This open access book explores the agenda of education policies in the 21st century. In the first part of the book, education is handled from a historical and political framework, and the effects of the change of states and policies on education are examined. In the second part, the effects of changes in the economy on education policies and economies' demands from educational institutions are examined. In the last section, current policies in the international education sector, which is growing day by day as a result of increasing globalization and internationalization, are examined and future trends are tried to be revealed. In articles written by academics from different universities all over the world, the topics are presented in a comparative perspective. Birol Akgün is president of Board of Trustees of Turkish Maarif Foundation and works as an academic member at Department of International Relations in Ankara Yıldırım Beyazıt University, Turkey. He has also taught at Selcuk University and Necmettin Erbakan University. Between 2004 and 2010, he served as Advisory Board Member for the Republic of Turkish Ministry of Foreign Affairs, Strategic Research Center. He was president of Strategic Thought Institute between 2014 and 2016. He is a member of the editorial board of many scientific journals. He took part in research projects about education, youth and social problems. His current research interests are international education, developing countries, international organizations and migration policies. Yusuf Alpaydın is working as a faculty member in the field of Educational Administration at Department of Educational Sciences in Marmara University, Turkey. Between 2003 and 2014, he worked as a school counselor in the educational institutions of the Ministry of National Education. During this period, He took part in various research and education projects, including curriculum, material development and formator training projects of the Family Training Program (AEP) of the Ministry of Family and Social Policies, Government of Turkey. He also actively works with various NGOs operating in the field of education and science. He was one of the founders of the Scientific Studies Association (İLEM) and served as the president for a term. He served as a board member and chairperson in the Association of Non-Formal Education and Culture.